1983
DOI: 10.1007/bf00223526
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of H1 histones

Abstract: The phosphorylation of H1 histones is reviewed. Consideration is given to phosphorylation reactions which occur in both replicating and nonreplicating cells. The available evidence suggests that H1 histones accept phosphate groups at different sites in response to different stimuli. The tentative location of the acceptor sites is summarized, and the effects of site-specific phosphorylation on the conformation of H1 histones in vitro is discussed. The phosphorylation of H1 histones which occurs during cell repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0
2

Year Published

1984
1984
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 59 publications
0
35
0
2
Order By: Relevance
“…Intriguingly, this higher sensitivity is especially pronounced during the progression of the cells from late-G1-phase into early-S-phase. Higher nuclease sensitivity is associated with relaxed chromatin structure, which potentially results from the elevated levels of histone H1 and H3 phosphorylation (Hohmann, 1983;Lu et al, 1994) within pRb-deficient cells at this time of the cell cycle due to deregulated cyclin-dependent kinase 2 (Cdk2) activity (Chadee et al, 1999;Herrera et al, 1996). Similar to the pRbdeficient primary fibroblasts, many transformed cell lines either lack pRb, or express mutant inactive pRb (Nevins, 2001;Niculescu et al, 1998).…”
Section: Journal Of Cell Science 115 (21)mentioning
confidence: 99%
“…Intriguingly, this higher sensitivity is especially pronounced during the progression of the cells from late-G1-phase into early-S-phase. Higher nuclease sensitivity is associated with relaxed chromatin structure, which potentially results from the elevated levels of histone H1 and H3 phosphorylation (Hohmann, 1983;Lu et al, 1994) within pRb-deficient cells at this time of the cell cycle due to deregulated cyclin-dependent kinase 2 (Cdk2) activity (Chadee et al, 1999;Herrera et al, 1996). Similar to the pRbdeficient primary fibroblasts, many transformed cell lines either lack pRb, or express mutant inactive pRb (Nevins, 2001;Niculescu et al, 1998).…”
Section: Journal Of Cell Science 115 (21)mentioning
confidence: 99%
“…Although it has been reported that the condensation of chromosomes during mitosis is linked to the phosphorylation of histones HI and H3 (Gurley et al, 1978;Bradbury and Mathews, 1981), the exact connection between these two events remains uncertain (Krystal and Poccia, 1981;Hanks et al, 1983;Hohmann, 1983). It is mentioned, however, that histone phosphorylation influences histone-DNA and histone-histone interactions and that it plays a role in differential gene activity (Allfrey, 1980;Bradbury and Matthews, 1981).…”
Section: Accessibility Of Various Histone Regions In Native or Hj/h5-mentioning
confidence: 99%
“…The number of phosphorylated residues is small in G 1 phase and starts to increase when the cell progresses through S and G 2 , reaching a maximal level at mitosis (28). Histone H1 phosphorylation is required for DNA replication (24), and protein kinases that activate replication also promote histone H1 phosphorylation (1).…”
mentioning
confidence: 99%